Foreword - Alison Diduck (UCL Journal of Law and Jurisprudence, 2019)
To download this paper, click here. I am delighted to introduce this issue of the UCL Journal of Law and Jurisprudence, the first of 2019. The journal first began to publish outstanding research by graduate students in 1994 as the UCL Jurisprudence Review. In 2012 it merged that review with the UCL Journal of Human Rights and the UCL Commercial Law Review and since then has been edited and run by UCL Laws students. It publishes cutting edge work by graduate students, academics and practitioners and this year the editors Joyman Lee, Andrew McLean (Academic Editors) and Luminita Olteanu (Managing Editor) have been ably assisted by an editorial board consisting of twenty-seven postgraduate students in bringing this issue to completion.